Leveraging Social Media to Enhance School Physical Activity and Promote Healthy Growth in Children - UMAR TANVEER,; ASGHAR, EJAZ (Pakistan Journal of Medical & Health Sciences, 2025)
Pakistan has historically prioritized education and sports as essential pillars for national development. However, emerging evidence highlights a troubling trend: Pakistani school-aged children and adolescents are engaging in insufficient physical activity (PA), experiencing rising rates of overweight and obesity, and exhibiting declining physical fitness.¹⁻⁷ Addressing this growing public health concern requires urgent reform in school physical education (PE) programs, alongside the strategic use of social media to raise awareness, inspire action, and promote healthy behavioral changes. Current Situation Research consistently documents the prevalence of unhealthy behaviors among Pakistani children and their association with obesity. Tanveer et al.¹ found that limited participation in school-based physical activity interventions significantly increased the risk of overweight and obesity. Additional studies on 24-hour movement behaviors² and sleep duration³ confirmed strong links between sedentary lifestyles and adverse health outcomes. Parental support⁴, nutrition patterns⁷, and access to community-level physical activity opportunities⁸ further influence children’s health behaviors. Despite this knowledge, fewer than 30% of students meet the global recommendation of at least 60 minutes of moderate-to-vigorous physical activity (MVPA) per day, while sedentary, screen-based activities continue to rise.¹⁷ Navigating the Challenges These trends reflect structural and sociocultural barriers within Pakistan’s education system. Heavy academic loads and the marginalization of PE reduce opportunities for active participation.⁵,⁶ In many schools, PE remains optional, hindered by limited infrastructure, insufficiently trained instructors, and lack of standardized curricula. Rural and underprivileged areas face even greater challenges, including unsafe environments and scarce sports facilities.⁶,⁸ Compounding these barriers are modern lifestyle factors such as prolonged screen time, video gaming, and smartphone use, which replace active play with sedentary entertainment.¹⁷ The Path Forward Strengthening PE as a mandatory and assessed component of school curricula is critical. Regular engagement in structured PE classes and school sports correlates with reduced obesity rates, improved fitness, mental resilience, social cohesion, and academic performance. Achieving these benefits requires a coordinated national strategy that ensures equitable implementation, adequate funding, and qualified instructors across all provinces. Social media presents a powerful opportunity to accelerate these efforts. With over 70 million internet users and a growing youth population, Pakistan can leverage digital platforms to promote PA, healthy nutrition, and reduced screen time. Campaigns led by educators, health professionals, and influencers can utilize engaging content—fitness challenges, short educational videos, and interactive competitions—to extend health promotion beyond the classroom. Evidence shows that digital engagement can effectively modify behaviors when combined with structured school interventions.¹⁹,²⁰ A national initiative involving the Ministry of Education, the Ministry of National Health Services, and social media organizations could replicate models like China’s “Healthy China 2030” by creating coordinated campaigns that emphasize gender equity and equal participation in sports.¹,²,⁵ Professional development for PE teachers and health educators, delivered via online platforms, can equip them with modern pedagogical skills and innovative teaching strategies. Schools should also conduct annual fitness assessments, using anthropometric and PA evaluation tools to guide policy and intervention efforts.⁵,⁶,¹¹ In conclusion, reversing the trend of physical inactivity and rising obesity in Pakistani children requires a comprehensive, evidence-based approach that integrates education reform, social media engagement, and community involvement. Without decisive action, these challenges may escalate into long-term public health crises, including cardiovascular disease and diabetes.¹⁷,²² By strengthening school PE, promoting parental and community support, and harnessing the power of digital media, Pakistan can foster a physically active, healthier generation ready to thrive in the future. The time to act is now. Financial support and sponsorship: None Conflict of interest: None declared.